The Use of Metaphors in Malcolm X Speech Entitled the Black Revolution - Yashinta Nur Wahyudi; Wijayadi -; Armeria Wijaya (Institut Agama Islam Negeri Palopo, 2022)
AbstractThis study analyzes the metaphor in Malcolm X's speech entitled The Black Revolution. The method used is qualitative descriptive method using the theory of Lakoff and Johnson (2003) and strengthened by the theory of Saeed (2005) in describing the characteristics contained in the metaphor. This analysis aims to identify the metaphors contained in Malcolm X's speech. The Black Revolution explains how oppression and injustice have been accepted by the black community in America over the years. The results of the research are Structural, Orientation, and Ontological metaphors. The most dominant metaphor used in speech is structural metaphor. Then there are the characteristics of Conventional, Systematic, Asymmetric, and Abstraction. The most dominant characteristic in speech is the systematic one.